Influence of maternal smoking during pregnancy on birth outcomes - Diabelková, Jana; Rimárová, Kvetoslava; Urdzík, Peter; Dorko, Erik; Bušová, Andrea; Andraščíková, Štefánia; Kaňuková, Lívia; Kluková, Dana; Drabiščák, Erik; Konrádyová, Nika; Škrečková, Gabriela (Central European Journal of Public Health, 2022)
OBJECTIVES: Smoking during pregnancy is causally associated with reduced birth weight and is strongly related to preterm birth. This study analyses the differences in birth outcomes between non-smokers and women who continued to smoke during pregnancy. METHODS: We conducted a study of 1,359 mothers who gave birth in 2017-2019 at the Department of Gynaecology and Obstetrics of Louis Pasteur University Hospital in Košice. Data on mothers and newborn infants have been reported from the birth book and from the reports on mothers at childbirth. For low birth weight we considered the weight of a newborn being less than 2,500 g and as for premature birth we referred to childbirth before pregnancy week 37. Two groups of mothers were classified according to the smoking habit during pregnancy and statistically processed in IBM SPSS Statistics 23.0. RESULTS: Infants born by women who smoked during pregnancy had the lower birth weight (2,769.0 grams on average) compared to non-smokers (3,224.1 grams) (p < 0.001). The differences in prevalence of premature birth have not been confirmed as statistically significant. Women who continued smoking during pregnancy were significantly more likely to be very young (OR = 5.9; 95% CI: 3.9-8.9; p < 0.001), unmarried (OR = 9.3; 95% CI: 6.1-14.0; p < 0.001), of lower level of education (OR = 39.6; 95% CI: 22.6-69.5; p < 0.001), and more likely to consume alcohol (OR = 6.6; 95% CI: 5.8-7.5; p < 0.01), and drugs (OR = 6.6; 95% CI: 5.8-7.5; p < 0.01) during pregnancy. When pregnant, they were most likely to see a doctor for the first time after the first trimester (OR = 0.1; 95% CI: 0.1-0.2; p < 0.001) and were more likely to see a doctor less than 8 times (OR = 6.1; 95% CI: 4.2-8.8; p < 0.001) during pregnancy. CONCLUSION: Tobacco prevention and cessation campaigns should focus on improving pregnancy outcomes in the future.
Keywords: komplikace těhotenství; porodní hmotnost; předčasný porod; Pregnancy; těhotenství; výsledek těhotenství; Pregnancy Complications; Premature Birth; Smoking; novorozenec; Pregnancy Outcome; lidé; ženské pohlaví; Birth Weight; Humans; Infant, Newborn; Infant, Low Birth Weight; Female; kouření; novorozenec s nízkou porodní hmotností